2021
DOI: 10.3233/jad-201088
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Diagnosis of the Frontal Variant of Alzheimer’s Disease with the DAPHNE Scale

Abstract: Background: The frontal variant of Alzheimer’s disease (fAD) is poorly understood and poorly defined. The diagnosis remains challenging. The main differential diagnosis is the behavioral variant of frontotemporal degeneration (bvFTD). For fAD, there is some dissociation between the clinical frontal presentation and imaging and neuropathological studies, which do not always find a specific involvement of the frontal lobes. DAPHNE is a behavioral scale, which demonstrated excellent performance to distinguish bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…The systematic literature search yielded 1257 records, of which 116 studies were assessed at full-text level for eligibility and 83 studies met inclusion criteria (eFigure 5 in the Supplement for flowchart). Confirmation of AD pathology was present in 91.1% of cases with bvAD based on autopsy data (36 studies; n = 334), genetic data (9 studies; n = 21), or biomarker data (31 studies; n = 262), while no information was available in 9.9% of cases (11 studies including 68 cases of bvAD). Thirteen studies were eligible for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic literature search yielded 1257 records, of which 116 studies were assessed at full-text level for eligibility and 83 studies met inclusion criteria (eFigure 5 in the Supplement for flowchart). Confirmation of AD pathology was present in 91.1% of cases with bvAD based on autopsy data (36 studies; n = 334), genetic data (9 studies; n = 21), or biomarker data (31 studies; n = 262), while no information was available in 9.9% of cases (11 studies including 68 cases of bvAD). Thirteen studies were eligible for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis was used to examine whether bvAD differed from tAD and bvFTD in terms of behavioral/neuropsychiatric and neuropsychological features and bvAD differed from tAD in the distribution of amyloid-β and tau pathology defined at autopsy. Missing data were requested from the authors of 3 studies (and all 3 responded) . We calculated the pooled standardized mean differences and 95% CIs using Hedges g random-effects models in the “meta” package of R version 4.0.2 (R Foundation for Statistical Computing), with a significance level of P < .05.…”
Section: Methodsmentioning
confidence: 99%
“…bvAD did not differ from tAD in three studies 23,26,27 , and showed moderately more involvement of frontal regions in bvAD compared to tAD in three other studies 17,24,25 . Studies assessing glucose metabolism with [ 18 F]FDG-PET or perfusion with SPECT (k=7, n=88) also showed heterogeneous results, ranging from a predominantly temporoparietal hypometabolic pattern 27,28 to a mixed frontal and temporoparietal 15,16,29,30 or predominantly frontal pattern 31 . Amyloid-PET studies (k=2, n=28) showed no differences in amyloid-β burden or distribution between bvAD and tAD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Missing data were requested from the authors of three studies (3/3 responded). [15][16][17] We calculated the pooled standardized mean differences and 95% confidence intervals using Hedges' g random-effects models in the "meta" package (R v4.0.2), with significance levels of p<0.05. We used random effects because we assumed that the true effect size would be study dependent, due to high heterogeneity in samples, methodology and outcomes among studies.…”
Section: Discussionmentioning
confidence: 99%
“…The DAPHNE scale 63 is based on the bvFTD diagnostic criteria 6 and on the FBI items. There is only one study to evaluate its application in the differential diagnosis between bvFTD and AD (frontal variant), with good clinical accuracy 64 . There is no Brazilian validation or translation of this scale, but it appears to be promising.…”
Section: Cognitive and Behavioral Assessmentsmentioning
confidence: 99%